The rights of Khiyar (option) in the issue of consumerism in Malaysia - Mohd Noor, Mohd Murshidi; Suliaman, Ishak; Ahmad, Khadher; Deraman, Fauzi; Abdullah, Mustaffa; Ahmad Shah, Faisal; Mohd Yusof, Mohd Yakub Zulkifli; Abd Razzak, Monika Munirah; Meftah, Jilani Touhami; Ariffin, Sedek; Kasar, Ahmad K.; Mohd Nor, Mohd Roslan (IDOSI Publications, 2013)
Khiyar or option is the right given to buyers and sellers whether to continue or to cancel their transactions. The objective of this article is to analyse the types of khiyar and to uncover its applications in the right of consumerism. In addition, this article analysed the connection between Contracts Act 1950 and Consumer Protection Act 1990 with the elements of khiyar that contain the rights of salesman and purchasers. The methodology applied in this research is the comparative method that comparatively study between the laws of Islam in khiyar and the acts related to the right of consumerism. The research discovers that khiyar al-'ayb (option due to deffects) can be applied due to its applicability with the existing laws in Malaysia. The research suggests that the concept of khiyar in Islamic law need to be applied into the existing law in Malaysia in order to preserve the interest for both consumers and sellers